Copolymers enhance selective bacterial community colonization for potential root zone applications. Issue 1 (December 2017) - Pham, Vy; Murugaraj, Pandiyan; Mathes, Falko; Tan, Boon; Truong, Vi; Murphy, Daniel; Mainwaring, David
Abstract Managing the impact of anthropogenic and climate induced stress on plant growth remains a challenge. Here we show that polymeric hydrogels, which maintain their hydrous state, can be designed to exploit functional interactions with soil microorganisms. This microbial enhancement may mitigate biotic and abiotic stresses limiting productivity. The presence of mannan chains within synthetic polyacrylic acid (PAA) enhanced the dynamics and selectivity of bacterial ingress in model microbial systems and soil microcosms.Pseudomonas fluorescens exhibiting high mannan binding adhesins showed higher ingress and localised microcolonies throughout the polymeric network. In contrast, ingress ofBacillus subtilis, lacking adhesins, was unaltered by mannan showing motility comparable to bulk liquids. Incubation within microcosms of an agricultural soil yielded hydrogel populations significantly increased from the corresponding soil. Bacterial diversity was markedly higher in mannan containing hydrogels compared to both control polymer and soil, indicating enhanced selectivity towards microbial families that contain plant beneficial species. Here we propose functional polymers applied to the potential root zone which can positively influence rhizobacteria colonization and potentially plant growth as a new approach to stress tolerance.